The right to strike under debate. Its construction within the specialized system, current controversy and its referral to the advisory jurisdiction of the International Court of Justice - Mendoza Legoas, Luis (2025)
The dispute that had place at the International Labour Organization regarding the exercise of the right to strike has propelled the Governing Body to refer the matter to the International Court of Justice, invoking its advisory jurisdiction. This is a serious matter as it reflects a crisis triggered by the employers’ group’s questioning about including the right to strike in the ILO Convention No. 87 and the capacity of the Committee of Experts on the Application of Conventions and Recommendations to interpret the respective standards. This issue may offer an opportunity to assess the complementarity of labour human rights protection systems and the suitability of the advisory opinion to be issued to contribute to restoring the functioning of ILO methods after this major incident.